Low-energy spin-polarized electrons: their role in surface physics - Tusche, Christian; Chen, Ying-Jiun; Schneider, Claus M. (Frontiers in Physics, 2024)
Low-energy (∼ 100eV) electrons have been employed for more than half a century to investigate physical, chemical and electronic phenomena in condensed matter and surface physics. A particular role may be attributed to a purely quantum-mechanical property of the electron -its spin or intrinsic angular momentum. Since the 1970's the electron spin has been indispensable in determining the role of spin-dependent interactions, such as exchange interaction and spin-orbit coupling and their consequences. Most recently, the aspect of topology and its role in condensed matter systems has given a new drive to the investigation of the electron spin and spin textures in such materials. New results on time-dependent ultrafast phenomena may become available by the availability of new intense lasers and laser-driven sources.